Do Happiness and Corruption Affect Tax Morale in Indonesia? An Empirical Analysis - Erina, Lili; Martina, Martina; Saptawan, Ardiyan (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2024)
When the government adopts a tax amnesty policy, it simultaneously indicates lower citizens' tax morale. Unlike previous studies that emphasized economic, regulatory, and tax service variables, this research attempts to analyze several attributes of the socio-economic life of taxpayers as determinants of tax morale. This study examines the effect of trust, corrupt practices in public services, happiness, and religiosity on the tax morale of Indonesian citizens. This cross-sectional study adopts a quantitative approach and utilizes secondary data from the 7th Word Value Survey (WVS) collected in 2017. The WVS respondents were 3,200 Indonesian citizens over 17 years old and spread across several provinces. Data were processed and analyzed using logistic regression. The authors argue that five independent variables influenced citizens' tax morale in Indonesia: the level of education, the perceptions of corruption practices in public services, the level of happiness, the job status, and religion. This research produces the characteristics of Indonesian citizens with high tax morale: educated, perceived corruption in public services, happy, employed, and Moslem. The result corroborates several previous studies that confirm a positive effect on happiness, education level, employment status, religion, tax morale and an adverse effect of corruption on tax morale. The authors recommend that the government increase access to quality/quantity of education, eradicate corruption, improve citizens' happiness, and create new jobs for citizens based on the spirit of inclusiveness (no one left behind).